Lycium barbarum Glycopeptide prevents the development and progression of acute colitis by regulating the composition and diversity of the gut microbiota in mice - Huang, Yichun; Zheng, Yinghui; Yang, Fengmei; Feng, Yicheng; Xu, Kunyao; Wu, Jun; Qu, Shuang; Yu, Zhexiong; Fan, Fu; Huang, Lu; Qin, Meng; He, Zhanlong; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
In most cases, recurrent chronic colitis is caused by the recurrence of acute colitis after incomplete recovery and re-exposure to irritating factors, and the gut microbiome, which is the largest micro-ecosystem in the human body, plays a crucial role in the development of colitis. Plant polysaccharides have always been reported to have the ability for anti-inflammation, and they are closely related to the gut microbiome. Lycium barbarum Glycopeptide (LbGP), the most potent component obtained by further isolation and purification from Lycium barbarum fruit, has been shown to inhibit inflammation in animal models. However, its therapeutic efficacy in colitis and its mechanism in gut microbiota regulation have not been fully studied. In our study, the dextran sulfate sodium (DSS)-induced mouse model was used to dynamically evaluate the effect of LbGP in the treatment of acute colitis and the mechanism from the perspective of the gut microbiome through the 16S rDNA sequence. The results showed that LbGP treatment significantly alleviated acute colitis and improved the gut microbiome compared with that in the model group. Harmful bacteria, such as Lachnoclostridium spp. and Parabacteroides_distasonis, were inhibited and probiotics, such as Bacteroides_acidifaciens, Lactobacillus spp., Turicibacter spp., and Alistipes spp., were increased by LbGP treatment. Further, a Random Forest analysis with 10-fold cross-validation identified a family named Muribaculaceae representing colitis development and recovery upon LbGP treatment. In conclusion, our study demonstrated the capability of LbGP to prevent the development of acute colitis by regulating the composition and diversity of the gut microbiota and highlighted the dynamic process of gut microbiota with the colitis progression. Further, it provides evidence to develop LbGP as a functional food supplement and future drug acting on intestinal disease.